PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN - Erlina Sari Pohan; Tri Lestari (Jurnal Akuntansi, 2018)
This study aims to examine the effect of Intellectual Capital by Value Added Intellectual Coefficient (VAICTM) on financial performance using market valuation (market to book value), profitability ratio Return On Asset (ROA) and Earning Per Share (EPS) and productivity ratio Asset Turnover (ATO) of the Information Tecnology and Services sector companies in BEI 2012-2016. The population of this study is companies of Information Tecnology and Services sector listed on the Stock Exchange from 2012 to 2016. The data processed using SPSS version 24.0. The results of this study indicate that intellectual capital proxied by Value Added Intellectual Coefficient (VAICTM) has a positive and significant effect on financial performance proxied by Market to Book Value, Return On Asset, Asset Turnover and Earning Per Share.